Hot and Cold Spot Analysis Using Stata. (September 2016) - Kondo, Keisuke
Spatial analysis is attracting more attention from Stata users because of the increasing availability of regional data. In this article, I present an implementation of hot and cold spot analysis using Stata. I introduce the new commandgetisord, which calculates the Getis–Ord G*i ( d ) statistic. To implement this command, one only needs the latitude and longitude of regions as the additional required information. In combination with shape files, the results obtained from thegetisord command can be visually displayed in Stata. In this article, I also offer an interesting illustration to explain how thegetisord command works.